On the systematic position of Electrocrania Kusnezov, 1941 with the description of a new species from Baltic amber (Lepidoptera: Micropterigidae) - Kurz, Michael (Zootaxa, 2015)
A new fossil species of Electrocrania Kusnezov is described, i.e. Electrocrania michalskii sp. nov. The male moth in Baltic amber is in a sufficiently good condition to allow its assignment to the family Micropterigidae on the basis of four re-cognized autapomorphies of this family (Kristensen 1998). The unique venation of the specimen places it in the genus Electrocrania stat. rev. and allows a redescription of that genus that has recently been treated as synonym of Micropterix Hübner. It is argued that Electrocrania is a distinct genus within Micropterigidae that is not associated with Micropterix, but probably can be assigned to the “Northern Hemisphere genera”-lineage of Micropterigidae.